Western life courses challenged in life stories collected in contemporary China - Cheng, Sheng-Li; Johansson, Stina; Liu, Shushan; Li, Yun (Frontiers in Public Health, 2023)
The life course describes the progression of life as a social role, from birth to death. Traditional Western life-history studies of the life course usually describe a continuous lifeline with occasional interruptions in between. The extraordinary temporal events of the Anti-Japanese War, Civil War, Great Famine, Cultural Revolution , and the Reform and Opening-up of China in just few decades mean that the life history of contemporary Chinese elderly people may be quite different from those of their western peers. The study used qualitative research methods to conduct in-depth interviews with 16 older adults and collect their life stories through a standardized list of questions. Findings are based on a generalized analysis of the cases, including an exploration of how the elderly who are now alive tell stories about lives characterized by recurring exceptional and rapidly changing environmental conditions and a discussion of the impact of such life experiences on individuals in the context of life course theory. We also suggest that education is an important part of the life story and that its value changes over time.